Deoxyalkylation of guaiacol using haggite structured V4O6(OH)4. Issue 8 (26th March 2019) - Yan, Fei; Wen, Zhe; Wu, Kai; Cui, Kai; Mai, Fuhang; Ma, Zewei; Sang, Yushuai; Bai, Yunfei; Chen, Hong; Li, Yongdan
Abstract : Haggite catalyzes the deoxygenation of guaiacol following the reverse Mars–van Krevelen mechanism. Abstract : When V2 O5 is used for the deoxygenation of guaiacol in methanol, it is reduced in situ to haggite structured V4 O6 (OH)4 . Guaiacol prevents further reduction of the haggite phase in methanol and haggite catalyzes the partial deoxygenation of guaiacol. Haggite is a metastable redox catalyst for the deoxygenation of guaiacol, which follows the reverse Mars–van Krevelen mechanism. In addition, haggite is also a Lewis acid catalyst and catalyzes the alkylation of guaiacol with methanol as the alkylation reagent. The main products of the guaiacol deoxyalkylation are 2, 6-dimethylphenol, 2-methoxy-6-methylphenol, 2, 4, 6-trimethylphenol, 2, 3, 6-trimethylphenol, 2, 3, 5, 6-tetramethylphenol and 6-methyl-2- tert -butylphenol. Oligomerization takes place during the reaction but it is reversible. When the reaction is performed at 300 °C for 6 h, the 83.5% total selectivity for alkylphenols is achieved with a 99.0% conversion.